Gonadotropin-releasing hormone agonist downregulation combined with hormone replacement therapy improves the reproductive outcome in frozen-thawed embryo transfer cycles for patients of advanced reproductive age with idiopathic recurrent implantation failure - Dan Pan; Jie Yang; Ni Zhang; Lei Wang; Na Li; Juanzi Shi; Hanying Zhou (BMC, 2022)
Abstract Background To determine whether gonadotropin-releasing hormone (GnRH) agonist downregulation combined with hormone replacement therapy (HRT) can improve the reproductive outcomes in frozen-thawed embryo transfer cycles for older patients (aged 36-43 years) with idiopathic recurrent implantation failure (RIF). Methods This retrospective cohort study involved 549 older patients undergoing their third cleavage-stage embryo or blastocyst transfer over a 5-year period (January 2015-December 2020) at Northwest Women's and Children's Hospital after in vitro fertilization/intracytoplasmic sperm injection cycles. Patients with known endometriosis or adenomyosis were excluded from the study. The patients were divided into three groups according to the endometrial preparation protocol: the natural cycle (NC) group (n = 65), the HRT group (n = 194), and the GnRH agonist downregulation combined with HRT cycle (GnRH agonist-HRT) group (n = 290). The primary outcome was the live birth rate, and the secondary outcomes were the clinical pregnancy, miscarriage, and ongoing pregnancy rates. Results The live birth rate in the GnRH agonist-HRT group (36.55%) was higher than that in the HRT group (22.16%) and NC group (16.92%) (P < 0.0001). Similarly, a logistic regression model adjusting for potential confounders showed that the live birth rate was higher in the GnRH agonist-HRT group than in the HRT group (odds ratio, 0.594; 95% confidence interval, 0.381-0.926; P = 0.021) and NC group (odds ratio, 0.380; 95% confidence interval, 0.181-0.796; P = 0.010). Conclusions The GnRH agonist-HRT protocol improves the live birth rate in frozen-thawed embryo transfer cycles for patients of advanced reproductive age with RIF. We hypothesize that the GnRH agonist-HRT protocol enhances implantation-related factors and promotes optimal endometrial receptivity, leading to an improved live birth rate. These findings are also useful for further investigating the underlying mechanism of the GnRH agonist-HRT protocol in improving the reproductive outcomes for patients of advanced reproductive age with RIF. Trial registration This research protocol was approved by the hospital institutional ethics committee (No. 2021002).